Management of seed borne ralstonia solanacearum in brinjal (Solanum melongena L.) and tomato (Lycopersicon esculentum Mill.) (Bangladesh Journal of Botany, 2024)
Total of 165 bacterial isolates of Ralstonia solanacearum were collected from different seed samples of tomato and brinjal in various seed sources and 22 isolates were tested to find out the management tools among different management approaches. Hundred percent reduction of bacterial incidence was found with Gentamicin (0.1, 0.05%), Erythromycin (0.1, 0.05%) and Doxycycline (0.1%) over control in both brinjal and tomato treated seeds in nutrient agar medium. Seed treatment with BAU-Biofungicide (3%) exhibited 83.61% decreases of bacterial incidence over control in tomato and 90.28% reduction in brinjal seeds. Garlic also showed better performance in controlling R. solanacearum among the plant extracts. Antibiotic sensitivity test revealed that maximum number of isolates of R. solanacearum was found to be sensitive to Gentamicin and Erythromycin, and the highest number of isolate of R. solanacearum of tomato and brinjal seeds marked resistant to Doxycycline. Higher germination 40.38% was achieved over control in tomato seed and 26.67% germination was in brinjal seed when the seeds were treated with BAU-Biofungicide (3%). Among all the treatments, BAU-Biofungicide (3%) also resulted in the highest increase of vigor index (77.36%) in tomato and brinjal seed with an increase of 69.91% over untreated control.Bangladesh J. Bot. 53(1): 173-183, 2024 (March)